2001
DOI: 10.1159/000047892
|View full text |Cite
|
Sign up to set email alerts
|

Bone Blood Flow and Vascular Reactivity

Abstract: Blood flow is essential for normal bone growth and bone repair. Like other organs, the regulation of blood flow to bone is complex and involves numerous physiologic mechanisms including the sympathetic nervous system, circulating hormones, and local metabolic factors. Our studies addressed the following questions: (1) Which endogenous vasoconstrictor agents regulate in vivo blood flow to bone? (2) Does a decrease in bone vascular reactivity to vasoconstrictor hormones account for the increase in blood flow dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…123 Besides carrying oxygen and nutrients to bone tissue, blood flow plays an active role in bone formation and remodelling by mediating the interactions among osteoblasts, osteocytes, osteoclasts, and vascular cells at a variety of levels. 124 Furthermore, sensitivity analysis suggests that smoking significantly affects the survival of implants inserted only in the maxilla. The lack of statistical significance for the mandible is surprising but is most likely explained by the limited number of studies 16,24,28,34,35 reporting implant survival for smokers and non-smokers exclusively in the inferior jaw.…”
Section: Discussionmentioning
confidence: 99%
“…123 Besides carrying oxygen and nutrients to bone tissue, blood flow plays an active role in bone formation and remodelling by mediating the interactions among osteoblasts, osteocytes, osteoclasts, and vascular cells at a variety of levels. 124 Furthermore, sensitivity analysis suggests that smoking significantly affects the survival of implants inserted only in the maxilla. The lack of statistical significance for the mandible is surprising but is most likely explained by the limited number of studies 16,24,28,34,35 reporting implant survival for smokers and non-smokers exclusively in the inferior jaw.…”
Section: Discussionmentioning
confidence: 99%
“…Besides carrying oxygen and nutrients to bone tissue, blood flow play an active role in bone formation and remodeling by mediating the interactions among osteoblasts, osteocytes, osteoclasts, and vascular cells at a variety of levels. (46) The uncoupled vessel density and blood perfusion implied a complex mechanism of nicotine in controlling angiogenic activity and blood perfusion. The reduced blood flow indicates that nicotine may produce vasoconstriction during bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…μCT data can be readily analyzed using advanced tools such as IPL software. For example, the thickness analysis shown in Figure 3C revealed that the main differences between cranial autograft and allograft are in vessels ranging from 0.1 to 0.08 mm in diameter, which characterizes blood arterioles 10 . This result is consistent with studies performed in long bone model 11 .…”
Section: Discussionmentioning
confidence: 99%